Toxicity due to release of microplastic fibres from disposable face masks on marine diatom Chaetoceros sp. and the role of EPS in combating the toxic effects - B.Y. Neethudas; Camil Rex M.; P.K. Suresh; Amitava Mukherjee (Emerging Contaminants, 2025)
Due to the COVID-19 pandemic, disposable face masks have become a significant source of microplastic pollution in marine ecosystems. Diatoms, as primary producers are often used as model organism for aquatic toxicity assessments. Only a limited number of studies have examined the toxicity of mask leachate (ML) on diatoms. However, the toxicity mechanism of ML released at different time intervals is underexplored. Furthermore, the role of extracellular polymeric substances (EPS) in modulating ML toxicity is also poorly understood. To address these gaps, we investigated the toxicity of ML from three time intervals (1-day, 14-day, and 21-day) on the marine diatom Chaetoceros sp., finding that toxicity increased with time: 21-day ML > 14-day ML > 1-day ML. To assess the toxicity, we have estimated chlorophyll pigment levels, reactive oxygen species, and malondialdehyde levels. Furthermore, the presence of heavy metals in the ML was analyzed using Inductively Coupled Plasma Mass Spectrometry. Our results suggest that increased ROS production is a crucial mechanism of toxicity, while EPS reduces toxic effects compared to pristine ML. The interaction of EPS with ML was analyzed using Fourier-Transform Infrared Spectroscopy and 3D-Excitation Emission Matrix spectroscopy. Pearson correlation and heatmap were used to assess the correlations between toxicity endpoints. This study provides critical insights into the environmental impact of ML on marine diatoms and highlights the role of EPS in mitigating ML toxicity.